2009
DOI: 10.1002/ange.200903199
|View full text |Cite
|
Sign up to set email alerts
|

A Polynuclear Lanthanide Single‐Molecule Magnet with a Record Anisotropic Barrier

Abstract: Dedicated to Professor Annie K. Powell on the occasion of her 50th birthday Single-molecule magnets (SMMs) continue to be an attractive research field because of their unique and intriguing properties and potential applications in high-density data storage technologies and molecular spintronics. [1] The anisotropic barrier (U) of an SMM is derived from a combination of an appreciable spin ground state (S) and uniaxial Ising-like magneto-anisotropy (D). [2] The magnet-like behavior can be observed by slow rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 52 publications
3
69
0
Order By: Relevance
“…The ac oscillating frequencies corresponding to the observed peak temperatures were also fitted to the Arrhenius law, which gave a U eff value of 32.3A C H T U N G T R E N N U N G (2.6) K and a t 0 value of 2.5A C H T U N G T R E N N U N G (1.1) 10 À10 s (Figure 7). The t 0 value is also in the normal range for SMMs/SIMs, [4][5][6][7][8][9][10] but it is remarkably smaller than that of 1 (5.6 10 À6 s), and the U eff value of 2 (32.3 K) is clearly smaller than that of 1 (74.1 K). Further research into the dynamic magnetic behavior of 2 in the form of c'' versus c' plots are shown in Figure 8.…”
Section: -10mentioning
confidence: 95%
See 2 more Smart Citations
“…The ac oscillating frequencies corresponding to the observed peak temperatures were also fitted to the Arrhenius law, which gave a U eff value of 32.3A C H T U N G T R E N N U N G (2.6) K and a t 0 value of 2.5A C H T U N G T R E N N U N G (1.1) 10 À10 s (Figure 7). The t 0 value is also in the normal range for SMMs/SIMs, [4][5][6][7][8][9][10] but it is remarkably smaller than that of 1 (5.6 10 À6 s), and the U eff value of 2 (32.3 K) is clearly smaller than that of 1 (74.1 K). Further research into the dynamic magnetic behavior of 2 in the form of c'' versus c' plots are shown in Figure 8.…”
Section: -10mentioning
confidence: 95%
“…À11 s for known SMMs/SIMs; [4][5][6][7][8][9][10] the U eff value is comparable to that of the star molecule Mn 12 [1] and is remarkably larger than that of the […”
Section: -10mentioning
confidence: 98%
See 1 more Smart Citation
“…The structures were solved by direct methods and refined by full-matrix least-squares analysis on F 2 using the SHELXL97 program package. CCDC 822912 (1), 822913 (2), and 822914 (3) contain the supplementary crystallographic data for this paper. These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/ data_request/cif.…”
mentioning
confidence: 99%
“…[2] Recently, high-nuclearity clusters as secondary building units (SBUs) acting as nodes have been introduced to construct diversiform inorganic-organic hybrid structures with organic ligands with different geometry as linkers. [3] Clusters as rigid SBUs, especially expanded to nanometer sizes, are better than single metal ion nodes at maintaining specific geometries and imparting physical properties to hybrids through the assembly process.…”
mentioning
confidence: 99%